The Effectiveness of Infection Prevention Control Nurse (IPCN) Supervision in Improving Safe Injection Compliance at RSUD Dr. R. Koesma Tuban - Mei Widyawati; Ryandini, Tiara Putri; Mokhamad Nurhadi; Lukman Hakim (Jurnal Penelitian Sekolah Tinggi Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Background: Compliance with safe injection standard operating procedures (SOP), in accordance with WHO recommendations, is an effort to prevent and control healthcare-associated infections. This is in line with the global commitment to improving the safety of patients and healthcare workers. Supervision is a reinforcing factor to improve compliance in performing safe intravenous injections. Method: The type of this research is correlational with a cross-sectional time approach. The respondents used in the study were 68 nurses and were selected using the cluster random sampling technique. The instrument used in data collection was a checklist. Result: The results of the statistical test using Chi Square with a significance level of α < 0.05 obtained a value of ρ = 0.001 < 0.05 with a correlation coefficient of r = 0.405, indicating a relationship between the two variables, categorized as moderate with a positive correlation. Conclusion: The conclusion of this study indicates a relationship between the implementation of IPCN supervision and efforts to improve safe intravenous injection practices at RSUD dr. R. Koesma Tuban.